Perkembangan Pasaran Sukuk Dalam Pasaran Modal Islam di Malaysia - Mohd Hussin, M. Y.; Muhammad, F.; Habidin, N. F.; Amirah, S. (Universiti Sains Islam Malaysia, 2024)
Islamic Capital Market (ICM) is an alternative component to the conventional capital market in Malaysia. This positive development of ICM has indirectly expanded the investment activity that is based on Shariah in Malaysia. Besides that, the role of Shariah Advisory Council (SAC) of Security Commission (SC) in preparing guidelines for people to be involved with Islamic investment field has encouraged the growth of ICM in Malaysia especially in Islamic Sukuk (bond) market.